Decoding Consumer Behavior: The Role of Pricing, Branding, and Social Media in Market Choices - Mukhammad Yusuf Ridwan; Lilik Indayani; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the impact of price, brand, and social media on consumer purchasing decisions within a regional textile market, employing a quantitative methodology. Data was collected through questionnaires and analyzed using multiple linear regression. Findings reveal that each factor significantly influences consumer behavior, suggesting that a holistic marketing strategy incorporating these elements is crucial for enhancing consumer engagement and retention. This research highlights the importance of synchronized marketing efforts in maximizing the effectiveness of pricing, branding, and digital engagement in regional markets. Highlights : Price, Brand, and Social Media Impact: Each factor significantly affects consumer purchasing decisions, emphasizing their critical role in marketing strategies. Holistic Marketing Approach: Integrating price, brand, and social media strategies is vital for enhancing market penetration and customer loyalty. Quantitative Analysis Validation: The use of multiple linear regression confirms the strong influence of these variables on consumer choices, supporting targeted marketing tactics. Keywords : Consumer Behavior, Pricing Strategy, Brand Influence, Social Media Marketing, Textile Industry